Bimbingan Belajar untuk Meningkatkan Motivasi Belajar Ekstrinsik - Eko Pramono; Arifin Nur Budiono; Azizah Aziz (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2020)
Based on the results of preliminary observations by the now major data and obtain the numbers in all schools of juvenile delinquency percentage 51%, after being given the action cycle I juvenile delinquency in schools has decreased by a large percentage of 48%, having resumed on cycle II juvenile delinquency rate has decreased by a large percentage of 74%.Thus the conclusion: the granting of individual counselling services showed that the intensity of juvenile delinquency in schools has decreased. Research activities have been successfully categorized karna percentages under the indicators of success that has been set by 80% the percentage of juvenile delinquency in schools. Thus with the granting of individual counselling services can lower the intensity of juvenile delinquency in schools class VIII in junior high school year Wuluhan Ulum Bustanul 2016/2017. Keywords: Individual Counselling, Juvenile Delinquency